The Relationship Knowledge and Attitudes of Patients in Preventing Hypertension Recurrence - Subari, Subari; Sulaiman, Sulaiman; Karjono, Karjono (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Hypertension is a major global health issue that significantly contributes to morbidity and mortality. This study examines the relationship between knowledge and attitudes towards preventing hypertension recurrence among hypertensive patients in Indonesia. Utilizing a cross-sectional design, data were collected from 49 hypertensive patients through questionnaires assessing knowledge and attitudes. The results reveal a significant correlation between good knowledge and positive attitudes, with 65% of those with good knowledge exhibiting a positive attitude compared to 35% among those with poor knowledge. The odds ratio (OR=1.643, p=0.000) indicates that patients with better knowledge are significantly more likely to have a positive attitude towards hypertension prevention. These findings underscore the importance of educational interventions in improving health outcomes. Tailored educational programs that address psychological and nutritional aspects, as well as social support mechanisms, are recommended to enhance patient knowledge and foster positive health behaviors. This study highlights the need for continuous patient education and support to reduce the recurrence of hypertension. Public health strategies should focus on integrating comprehensive educational approaches to empower patients and improve adherence to hypertension management practices. The significant role of education in shaping health attitudes and behaviors emphasizes its critical place in public health initiatives aimed at combating hypertension.